Cercárias das superfamílias Diplostomoidea, Echinostomatoidea e Plagiorchioidea em moluscos do Brasil: novos registros baseados na abordagem taxonômica integrativa - Danimar Danilia Lopez Hernandez (2022)
Trematodes belonging to the superfamilies Echinostomatoidea, Plagiorchioidea and Diplostomoidea are, as adults, parasites of tetrapods. These helminths have complex biological cycles, involving gastropod mollusks and different invertebrates as first intermediate hosts and vertebrate species as secondary hosts. More than 250 trematodes species of these three large groups have been recorded infecting brazilian vertebrates, several of them with medical-veterinarian importance. However, in most of these species, the biological cycle and the mollusk transmitters are unknown. In the present study, larvae of echinocercariae, xyphidiocercariae and strigeocercariae types, obtained from mollusks collected in water bodies in Brazil, were subjected to morphological and molecular studies. The samples correspond, in part, to previously collected larvae in localities from the states of Minas Gerais, Maranhão and Rio de Janeiro between 2013 and 2019 (35 samples). In addition, obtained larvae during malacological collections carried out in localities of Minas Gerais between 2018 and 2019 were also evaluated. In this case, 1706 gastropod mollusk specimens of 11 species were examined and 95 were infected by larvae of the superfamilies of interest (11 samples). The obtained larvae were subjected to morphological and morphometric studies under optic microscope and compared with similar larvae reported in Brazil and other parts of the world. Molecular study resulted in 67 nucleotide sequences of nuclear (28S and ITS1-5.8S-ITS2) and mitochondrial (Cox- 1 and Nad-1) genes. These were compared with sequences available in GenBank and used in phylogenetic analyses (Maximum Likelihood and Bayesian Inference). Most of evaluated samples correspond to larvae of the superfamily Echinostomatoidea, identifying 12 species from 2 families. The Echinostomatidae family was represented by 11 species including Drepanocephalus spathans, Neopetasiger sp., Echinostomatidae sp. 1, Echinostomatidae sp. 3, Echinostomatidae sp. 4, Echinostomatidae sp. 5, Rhopalias sp. 1, Rhopalias sp. 2, Rhopalias sp. 3 and Ribeiroia sp. founded in planorbid mollusks (Biomphalaria spp., Drepanotrema lucidum and Gundlachia ticaga), as well as Echinostomatidae sp. 2 found in Pomacea sp. One species was identified to family level, Echinochasmidae gen. sp., was verified in Pomacea spp. Also, magnacauda-like larvae with cephalic collar with 19 spines were associated with the genus Neopetasiger, which includes species found in birds. On the other hand, biological cycle of species of the genus Rhopalias, marsupial parasites, was demonstrated for the first time, based on the study of Cercaria macrogranulosa. In the superfamily Plagiorchioidea, 5 samples of 13 xyphidiocercariae were studied, including larvae widely reported in Biomphalaria spp. in Brazil, Cercaria minense, Cercaria lutzi and Cercaria santense, which were identified as Magnivitellinum sp. (fish parasite), Haematoloechidae gen. sp. (amphibian parasite), Plagiorchioidea gen. sp., respectively. In addition to these, the presence of cercariae of the snake parasite Renifer sp. in Stenophysa marmorata is recorded for the first time in South America. Larvae of a probable amphibian lung parasite, Haematoloechus sp. were found in Pseudosuccinea columella. In the superfamily Diplostomoidea new information was added for 3 species found for the country. One of these, derived from Biomphalaria straminea, was identified as Apharyngostrigea pipientis. This is a species that parasitizes ardeids and the obtained results contributed to characterize its intercontinental distribution. Finally, two species of the family Diplostomidae are also reported. One of them, associated with "black spot disease" in fish, was identified as Crassiphiala sp. using B. straminea and ornamental fish, Etroplus maculatus, as intermediate hosts. Another larva was identified as Diplostomidae gen. sp., showing no morphological or molecular similarity to any of the larvae and sequences available for comparison. The results presented here revealed a variety of new biological interactions between mollusks and trematode larvae in Brazil. On the other hand, the generation of reference sequences (based on adults) for the Neotropical trematode fauna is essential to advance in cercariae identification found in mollusks.